PENGARUH UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Barang Produksi dan Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Patriandari; Cindi Agmi Cahyani Putri (RELEVAN : Jurnal Riset Akuntansi, 2021)
This study aims to determine the effect of Company Size and Capital Structure on Firm Value. The sample used in this study is a company listed on the Indonesia Stock Exchange, published financial reports in 2015 - 2019 with 10 sample companies using the purposive sampling method. The independent variable of this study is the size of the company as measured by size and capital structure as measured by the Debt to Equity Ratio. The dependent variable of this research is Firm Value as measured by Price to Book Value. The results show that firm size and capital structure have a positive and significant effect on firm value.